KONTRIBUSI RATING NIELSEN AUDIENCE MEASUREMENT INDONESIA (Pada Sinetron Tukang Bubur Naik Haji The Series di RCTI) - Haryanto, Dwi (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2017)
Tukang Bubur Naik Haji is a television series on RCTI carrying religious and comedy genres. The popularity and continuation of Tukang Bubur Naik Haji: The Series since its beginning of the show on May 28, 2012 has ignited the issue that rating also contributes in maintaining the series continuation. The research is conducted to discuss about the contribution of rating based on Nielsen Audience Measurement Indonesia to thecontinuation of Tukang Bubur Naik Haji: The Series. The purpose of the research is to know the contribution given the research media to the success of a television show program as well as given the rating by Nielsen Audience Measurement Indonesia to the continuation of Tukang Bubur Naik Haji: The Series on RCTI. The result of the research is that the rating based on Nielsen Audience Measurement Indonesia plays an important role in the continuation of Tukang Bubur Naik Haji: The Series because in television industry business, rating is the currency used to sell the slot of shows as how Tukang Bubur Naik Haji offers to the advertising.